2020
DOI: 10.3389/fphar.2020.587689
|View full text |Cite
|
Sign up to set email alerts
|

Potential Targeting of Renal Fibrosis in Diabetic Kidney Disease Using MicroRNAs

Abstract: Diabetic kidney disease (DKD) is a major health problem and one of the leading causes of end-stage renal disease worldwide. Despite recent advances, there exists an urgent need for the development of new treatments for DKD. DKD is characterized by the excessive synthesis and deposition of extracellular matrix proteins in glomeruli and the tubulointerstitium, ultimately leading to glomerulosclerosis as well as interstitial fibrosis. Renal fibrosis is the final common pathway at the histological level leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 89 publications
0
19
0
Order By: Relevance
“…Moreover, podocyte apoptosis is known to be controlled by miR-29c and miR-21, and when miR-29c expression increases, it promotes fibronectin assembly and apoptosis [ 171 ]. The noncoding RNA miR-let-7 decreases ECM protein expression through a mechanism that involves the TGF-β/Smad3 pathway [ 172 ], and DPP-4 inhibition and promotion of peptide AcSDKP expression result in renal protection by regulating crosstalk between miR-29 and miR-let-7 [ 173 ].…”
Section: Epigenetic Modifications and The Pathogenesis Of Dkdmentioning
confidence: 99%
“…Moreover, podocyte apoptosis is known to be controlled by miR-29c and miR-21, and when miR-29c expression increases, it promotes fibronectin assembly and apoptosis [ 171 ]. The noncoding RNA miR-let-7 decreases ECM protein expression through a mechanism that involves the TGF-β/Smad3 pathway [ 172 ], and DPP-4 inhibition and promotion of peptide AcSDKP expression result in renal protection by regulating crosstalk between miR-29 and miR-let-7 [ 173 ].…”
Section: Epigenetic Modifications and The Pathogenesis Of Dkdmentioning
confidence: 99%
“…miRNAs are single stranded non coding RNA molecules mainly involved in regulating gene expression [ 22 ]. Notably, miRNAs are increasingly demonstrated to act as key regulators of genes involved in the pathophysiology of various diseases, including kidney fibrosis [ 23 , 24 ]. One of the most widely reported miRNA is the miR29 family, which is composed of three extremely similar orthologues (miR29a, miR29b, and miR29c) that share identical seed binding sequences and the ability to bind to similar target genes [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the cluster analysis and the timeline view of references, we could find that microRNAs (miRNAs) are not only the largest clustering but also the emerging research Frontier in recent years. More attention has been paid to miRNAs for their potential fibrotic or antifibrotic effects (29). Researchers found that the dysregulated expression of miRNAs accelerated the ECM accumulation and stimulated pro-fibrotic signaling, finally leading to renal fibrosis (30).…”
Section: Discussionmentioning
confidence: 99%